Adverse reactions to vancomycin and cross-reactivity with other antibiotics. Issue 4 (August 2020) - De Luca, Joseph F.; Holmes, Natasha E.; Trubiano, Jason A.
Abstract : Purpose of review: Glycopeptide antibiotics such as vancomycin are frequently utilized to treat resistant Gram-positive infections such as methicillin-resistant Staphylococcus aureus . The current literature on glycopeptide and lipoglycopeptide structure, hypersensitivity and potential cross-reactivity was reviewed, highlighting implications for safe prescribing. Recent findings: Structurally similar, glycopeptides could theoretically cross-react. Immediate reactions to vancomycin include non-IgE-mediated reactions (e.g. red man syndrome) and IgE-mediated hypersensitivity (e.g. anaphylaxis), sharing clinical features. Vancomycin can activate mast cells via MAS-related G-protein-coupled receptor X2, an IgE-independent receptor implicated in non-IgE reactions. In-vivo and in-vitro testing for suspected IgE-mediated reactions to glycopeptides remain ill-defined. Vancomycin is increasingly recognized to cause severe cutaneous adverse reactions (SCAR), with drug reaction with eosinophilia and systemic symptoms (DRESS) predominantly reported. Vancomycin DRESS has been associated with HLA-A * 32:-01, with a number needed to prevent of 1 in 74. Data demonstrating cross-reactivity amongst glycopeptides and lipoglycopeptides is limited to case reports/series. Summary: Further studies and in-vivo / in-vitro diagnostics are required for better differentiation between IgE and non-IgE glycopeptide reactions. Despite its association with vanomycin DRESS, utility of pharmacogenomic screening for HLA-A * 32: 01 is ill-defined. Although HLA-A * 32:01 has been associated with vancomycin DRESS, its utility for pharmacogenomic screening is ill defined. Further clinical and immunological cross-reactivity data for glycopeptide/lipoglycopeptide antibiotics is required.